Parental disclosure of positive BRCA1/2 mutation status to children 10 years after genetic testing. Issue 6 (2nd July 2020) - Troïan, Jaïs; Apostolidis, Thémis; Touzani, Rajae; Mouret-Fourme, Emmanuelle; Stoppa-Lyonnet, Dominique; Lasset, Christine; Berthet, Pascaline; Julian-Reynier, Claire; Mancini, Julien; Noguès, Catherine; Bouhnik, Anne-Déborah
ABSTRACT: The disclosure of genetic information is an important issue in cancer prevention. This study based on a French national cohort of BRCA1/2 mutation carriers (GENEPSO-PS cohort, N=233 ) aimed to assess the prevalence of parental disclosure of genetic information to children 10 years after genetic testing, with a focus on gender differences. Most participants (n = 193, 131 women) reported having children. A total of 72.0% of offspring had received genetic information (88.8% for adult offspring, p < .001), with no differences according to the gender of the mutation-carrying parent. While female carriers disclosed genetic information more often than male carriers (54.1% versus 38.3%, p = .029), they did so irrespective of the gender of their offspring. Moreover, female carriers who had developed incident cancer after genetic testing disclosed genetic information more frequently than unaffected female carriers (70.7% versus 48.5%, p = .005). A multivariate analysis confirmed the effects of both gender and cancer on disclosure to offspring. The same results were obtained when the analysis was restricted to adult offspring. This study reveals high rates of disclosure of positive BRCA1/2 mutation status to children 10 years after genetic testing, irrespective of the gender of the carrier/offspring. However, female carriers disclosed genetic information more frequently than male carriers.